Padrões de distribuição e a conservação das aves passeriformes da caatinga - SOUZA, Manuella Andrade de (Universidade Federal do Pará, 2013)
The Caatinga is an exclusively Brazilian biome mainly located in the Northeast region. This ecosystem is little studied and is also one of the most threatened and altered by humans. The aim of this study was to determine the areas with highest richness of passeriforms, to identify how these species are distributed and how they use habitat resources. Moreover, we tested the efficiency of Conservation Units and Priority Areas proposed by PROBIO to protect endemic and threatened taxa. Most of the 273 taxa of passeriforms recorded for the Caatinga depend direct or indirectly upon forests to survive. A number of 37 taxa were registered as endemic for the region, of these 26 are dependent of forest. The areas of higher richness are directly related to habitat diversity. A total of 10 most important priority areas were identified for the conservation of endemic and threatened passerines. In addition to covering only a reduced area of the ecosystem, the conservation units do not fully represent the endemic and threatened taxa for the biome. Thus, an efficient system of conservation of the Caatinga shall consider the landscape diversity, especially for the conservation units forested areas and caatinga-like neighbouring vegetation.